Globalisasi Sebagai Katalis Kosmopolitanisme dan Multikulturalisme: Studi Kasus Resistance Cina Terhadap Kosmopolitanisme - Hardi Alunaza SD; Moh. Sarifudin (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2017)
This research is attempted to answer and explain on how the similarities and the differences between cosmopolitan and multiculturalism in case of China’s resistance towards the cosmopolitan phenomenon. This is a descriptive research with qualitative approach. The data collection method in this research is through library with secondary data sources by using the concept of Cosmopolitanism and Multiculuralism. Analysis is conducted by referring Globalization as a pattern that creates an increasingly obvious dependence relationship with the loss of state boundaries in the process of economic, political, and cultural integration. Globalization has also given chance to Cosmopolitanism and Multiculturalism that is currently growing rapidly around the world. The results shows and explains that globalization is functioned as catalyst between Cosmopolitanism and Multiculturalism. In China’s case it could be said that the cosmopolitanism is in two ways: the market cosmopolitanism and the international-federation cosmopolitanism.